METHODS FOR CALCULATING RECTANGULAR SECTION BEAMS MADE OF WOOD AND CONCRETE - Dubrakova, Ksenia Olegovna; Aseev, Viacheslav; Bulgakov, Aleksey (Journal of Applied Engineering Science, 2021)
The research aimed to study methods for calculating wood-concrete beams of rectangular cross-section when testing building structures according to the ultimate limit state. The article focuses on the comparison of theoretical methods for calculating structures and considers several methods of fastening the samples of a typical wood-concrete beam. There were obtained experimental data of the ultimate limit state for each sample and carried out a comparative analysis of the most advantageous scheme of fastening the sample parts. The scientific novelty is in the development of an algorithm for calculating composite wood-concrete beams of rectangular cross-sections. As a result, numerical comparison of the values for calculating a typical wood-concrete beam using two of the methods under consideration was given, experimental studies were carried out, as well as a comparative analysis of the obtained theoretical and experimental results.
Keywords: wood-concrete connection, wood-concrete structures, concrete-wood structured mine